Characterization of Broad Spectrum Bacteriophage vB ESM-pEJ01 and Its Antimicrobial Efficacy Against Shiga Toxin-Producing Escherichia coli in Green Juice - Eun Jeong Park; Seungki Lee; Jong Beom Na; Ye Bin Kim; Kee Man Lee; Seon Young Park; Ji Hyung Kim (Microorganisms)
Shiga toxin-producing Escherichia coli (STEC) infections have increased in humans, animals, and the food industry, with ready-to-eat (RTE) food products being particularly susceptible to contamination. The prevalence of multidrug-resistant strains has rendered the current control strategies insufficient to effectively control STEC infections. Herein, we characterized the newly isolated STEC phage vB_ESM-pEJ01, a polyvalent phage capable of infecting Escherichia and Salmonella species, and assessed its efficacy in reducing STEC in vitro and food matrices. The phage, belonging to the Tevenvirinae, exhibits effective bacteriolytic activity, a short latent period, large burst size, and stability under a broad pH range and moderate temperatures. Moreover, the phage demonstrated strong anti-biofilm efficacy even at low concentrations. Genomic analysis revealed that the phage was similar to the well-characterized RB49 phage (T4-like phage) but possesses distinct host-specificity-related genes that potentially contribute to its extensive host range. The efficacy of phage vB_ESM-pEJ01 was evaluated in artificially STEC-inoculated green juice samples, where it significantly reduced STEC and the abundance of Shiga toxin-producing genes at 4 and 25 °C. Therefore, these results suggest that the polyvalent phage vB_ESM-pEJ01 is a promising biocontrol agent for foodborne pathogens in RTE foods such as fresh juices.